Lathrolestes Förster, 1869 (Hymenoptera, Ichneumonidae) from Brazil, with description of two new species and a key to the Neotropical species - Lima, Alessandro Rodrigues; Kumagai, Alice Fumi (Zootaxa, 2016)
The taxonomic knowledge about Brazilian Ichneumonidae species is still incipient, especially for groups poorly represented in the Neotropics, like Ctenopelmatinae. The genus Lathrolestes Förster, 1869, mainly Holarctic, is here recorded for the first time to Brazil, with description of L. piranga Lima & Kumagai sp. n. and L. pitunauassu Lima & Kumagai sp. n. Additionally, a key to the Neotropical species is provided.